Improving Mathematics Learning Outcomes Using The Mind Mapping Method for Students of SMPN 8 Denpasar - Widana, I Wayan; Umam, Eka Koirul (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study is a classroom action research that aims to improve mathematics learning outcomes. The research was conducted at SMPN 8 Denpasar, which is located on Jl. Meduri No. 2, Sumerta Village, East Denpasar District, Denpasar City, Bali. The research subjects were 40 class VIII-A students of SMPN 8 Denpasar semester 2 of the 2022/2023 academic year. The object of research is the mathematics learning outcames. Data on learning outcomes were collected using tests, and analyzed descriptively qualitatively. Criteria for the success of the research: (a) the average value of class is at least to classical completeness criteria of 70 and (b) classical completeness of at least 85%. The results showed that in the first cycle the average value of class was 73.70 with classical completeness 52.50%; in cycle II the average value of class was 81.30 with classical completeness of 87.50%. Thus, it can be concluded that the Mind Mapping method is able to improve the mathematics learning outcomes of class VIII-A students of SMPN 8 Denpasar semester 2 of the 2022/2023 academic year in 2 cycles.